Qu'est-ce qu'une minorité ? - Deschênes, Jules (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
With a view to defining what a minority is, the author lays down an inventory of variables likely to aid in answering the above question. Hence we find the minority's « will to survive » and the « number of its members ». In his research, the author leads us to consider various legal, para-legal and doctrinal opinions from which we may extract several constants that permeate the whole. Thus it is that down through the decisions of the Permanent Court of International Justice, the European Court for Human Rights, Canadian courts, etc., there are various elements defining what a minority is.